2001
DOI: 10.1212/wnl.57.5.790
|View full text |Cite
|
Sign up to set email alerts
|

The use of alternative therapies by patients with Parkinson’s disease

Abstract: The use of AT is common in patients with PD. The age at onset of PD is the most potent predictor of AT use. There is no association between the use of AT and the severity of PD. The widespread and largely unexamined use of AT for PD requires more attention. This should be directed at testing their safety and efficacy and improving physician and patient knowledge about the potential benefits, costs, limitations, and risks of AT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
103
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(120 citation statements)
references
References 26 publications
10
103
7
Order By: Relevance
“…58 However, in a sample of those with anxiety and depression, 71 no sociodemographic variables were predictors of CAM use. No studies indicated that not being married was associated with CAM use.…”
Section: Marital Statusmentioning
confidence: 93%
See 1 more Smart Citation
“…58 However, in a sample of those with anxiety and depression, 71 no sociodemographic variables were predictors of CAM use. No studies indicated that not being married was associated with CAM use.…”
Section: Marital Statusmentioning
confidence: 93%
“…51,58,67,68 For instance, in a study of veterans with pain, 68 CAM use was associated with an income greater than $50 000/year (91.2% vs 8.8%, P = .006). This was also the case in a study of those with Parkinson's disease, 58 where those with higher income levels were associated with CAM use (χ 2 not given, P = .038). Somewhat related to income level, those who were employed were associated with CAM use.…”
Section: Incomementioning
confidence: 99%
“…Complementary and alternative therapy is being used more often as a complementary treatment to Western medicine for patients with PD [24][25][26][27]. As many as 40% of patients with PD use some form of complementary medicine during the course of their illness [28], and among these, acupuncture is popular [1]. Acupuncture has been reported to have a neuroprotective effect in PD animal models [4,[29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps in light of these limitations, holistic interventions that address the motor and non-motor symptoms of disease simultaneously are gaining popularity. Surveys of outpatient PD clinics suggest that 40-50% of patients with PD in the US use some form of complementary and integrative medicine (CAIM) modality, and up to 7.5% of all adults participate in yoga [9,10]. Neurologic disorders may be particularly amenable to mind-body therapies -therapies that treat the mind and emotions as well as the physical limitations associated with a disease.…”
Section: Introductionmentioning
confidence: 99%
“…Treatments like yoga involve stress-relieving practices which may be particularly relevant in neurologic conditions such as PD which are often exacerbated by stress [9]. In addition, CAIM therapies have been described as empowering to patients -making them active participants in their healthcare in ways that pharmacologic and surgical treatments cannot [9,10]. Despite the wide utilization of CAIM and yoga-based therapies there is a relative paucity of evidence in support of their use in PD and other related neurological patient samples.…”
Section: Introductionmentioning
confidence: 99%